Analysis of the long jump technique in the transition from approach to takeoff based on time-continuous kinematic data - Jaitner, T.; Mendoza, L.; Schöllhorn, W. I. (European Journal of Sport Science, 2001)
There are many studies on the biomechanics of the long jump, but few researchers have investigated how the athlete has to perform the last strides in order to prepare for takeoff. In this investigation, a pattern recognition approach was applied to analyze the movement structure during the last strides of the approach run and the jump. Time-continuous kinematic data of 57 trials (4.45-6.84 m) was analyzed. Cluster analysis identified at coarse level different movement patterns for each flight and support phase. Above these structural differences, individual movement patterns were diagnosed, especially for the jump. Further, the contribution of single variables on the differences of the complex movement patterns was determined by discriminant analysis. Based on the results, conclusions were drawn concerning the long jump and individuality in training. Overall, the applied pattern recognition method allows for the identification of structural changes of movement patterns as well as individual movement styles. This offers a wide range of application in various areas like sports training and rehabilitation.